Analysis of the national structure of care provided toolder people in Slovenia - Hlebec, Valentina (Metodološki zvezki, 2023)
Ageing in place has for many years been at the forefront of political goals for care provisionfor older people in Europe. The organization of care in terms of the national governingstructure must therefore be continually observed to better understand the care actuallyoffered and then used by older people. In this study, we examined the organization ofsocial home care and institutional care across municipalities and administrative units interms of what is offered to older people as formal care. Variation across municipalities andadministrative units is observed with explorative cluster analysis and analysis of meansof key dependent variables across clusters to better understand the variability in the careoffered to older people in those municipalities and administrative units. The results showthat while social home care is temporally available across several clusters of municipalities,and the affordability of social home care is also stable across clusters of municipalities,there are still municipalities where social home care has a limited time availability andmunicipalities where the out-of-pocket contribution to social home care delivery is nearlythe twice the average of such contributions. In terms of institutional care, one can findadministrative units with either a deficit or a surplus of placements of such care available.
Keywords: ageing in place; care organization; care policy; home care; Oskrba starostnikov; Starostniki